2019
DOI: 10.3171/2018.5.jns18583
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Gamma Knife radiosurgery versus microvascular decompression following failure of GKRS in trigeminal neuralgia: a systematic review and meta-analysis

Abstract: OBJECTIVEGamma Knife radiosurgery (GKRS) has emerged as a promising treatment modality for patients with classical trigeminal neuralgia (TN); however, considering that almost half of the patients experience post-GKRS failure or lesion recurrence, a repeat treatment is typically necessary. The existing literature does not offer clear evidence to establish which treatment modality, repeat GKRS or microvascular decompression (MVD), is superior. The present study aimed to compare the overall outcome of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
13
2
1
Order By: Relevance
“…A number of systematic reviews and meta-analyses compared GKRS with microvascular de-compression (MVD), which will be discussed below in connection with MVD, the only treatment that directly corrects the cause of TN in at least 50% of cases [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of systematic reviews and meta-analyses compared GKRS with microvascular de-compression (MVD), which will be discussed below in connection with MVD, the only treatment that directly corrects the cause of TN in at least 50% of cases [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, retreatment rates are higher for GKRS than for MVD, 17% vs. 10.3%, though the difference is not statistically significant (OR, 1.76; 95% CI, 0.93–3.55; p = 0.08). However, a systematic review and meta-analysis found that once GKRS had failed, there was no difference in the outcome between repeat GKRS and MVD [ 72 ]. One possible factor contributing to this is that the initial choice in selecting GKRS could have been based on the lack of neurovascular compression.…”
Section: Discussionmentioning
confidence: 99%
“…The literature overall suggests that outcomes for TN after repeat SRS are comparably good, or better, than after the initial SRS; however, the toxicity is higher [25-27]. A recent meta-analysis by Patra et al [28] found no difference between repeat SRS and MVD in producing adequate pain relief (BNI I–III) for recurrent TN at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…117 When GKRS fails, MVD may provide better likelihood of complete pain relief as opposed to repeat GKRS. 118 MVD may pose small risk (less than 3% each) of incisional infection, facial palsy, CSF leak and hearing deficits and risk of mortality was 0.1%. 119…”
Section: Surgical Treatmentmentioning
confidence: 98%